Worse progression of COVID‐19 in men: Is testosterone a key factor? - Giagulli, Vito A.; Guastamacchia, Edoardo; Magrone, Thea; Jirillo, Emilio; Lisco, Giuseppe; De Pergola, Giovanni; Triggiani, Vincenzo (Andrology (Oxford), 2021)
Background The novel severe acute respiratory syndrome coronavirus (SARS‐CoV‐2) disease 2019 (COVID‐19) seems to have a worse clinical course among infected men compared with women, thus highlighting concerns about gender predisposition to serious prognosis. Therefore, androgens, particularly testosterone (T), could be suspected as playing a critical role in driving this excess of risk. However, gonadal function in critically ill men is actually unknown, mainly because serum T concentration is not routinely measured in clinical practice, even more in this clinical context. Objective To overview on possible mechanisms by which serum T levels could affect the progression of COVID‐19 in men. Methods Authors searched PubMed/MEDLINE, Web of Science, EMBASE, Cochrane Library, Google, and institutional websites for medical subject headings terms and free text words referred to “SARS‐CoV‐2,” “COVID‐19,” “testosterone,” “male hypogonadism,” “gender” “immune system,” “obesity,” “thrombosis” until May 19th 2020. Results T, co‐regulating the expression of angiotensin‐converting enzyme 2 and transmembrane protease serine 2 in host cells, may facilitate SARS‐CoV‐2 internalization. Instead, low serum T levels may predispose to endothelial dysfunction, thrombosis and defective immune response, leading to both impaired viral clearance and systemic inflammation. Obesity, one of the leading causes of severe prognosis in infected patients, is strictly associated with functional hypogonadism, and may consistently strengthen the aforementioned alterations, ultimately predisposing to serious respiratory and systemic consequences. Discussion and conclusion T in comparison to estrogen may predispose men to a widespread COVID‐19 infection. Low serum levels of T, which should be supposed to characterize the hormonal milieu in seriously ill individuals, may predispose men, especially elderly men, to poor prognosis or death. Further studies are needed to confirm these pathophysiological assumptions and to promptly identify adequate therapeutic strategies.